Extracellular vesicles in heart failure – A study in patients with heart failure with preserved ejection fraction or heart failure with reduced ejection fraction characteristics undergoing elective coronary artery bypass grafting - Matan, Dmitri; Mobarrez, Fariborz; Löfström, Ulrika; Corbascio, Matthias; Ekström, Mattias; Hage, Camilla; Lyngå, Patrik; Persson, Bengt; Eriksson, Maria; Linde, Cecilia; Persson, Hans; Wallén, Håkan (Frontiers in Cardiovascular Medicine, 2022)
Aims: Extracellular vesicles (EVs) were investigated as potential biomarkers associated with heart failure (HF) pathophysiology in patients undergoing elective coronary artery bypass surgery characterized by HF phenotype. Methods: Patients with preoperative proxy-diagnoses of HF types i.e preserved (HFpEF; n=19) or reduced ejection fraction (HFrEF; n=20) were studied and compared to patients with normal left ventricular function (n=42). EVs in plasma samples collected from the coronary sinus, an arterial line, and from the right atrium were analyzed by flow cytometry. We studied EVs of presumed cardiomyocyte origin (EVs exposing Connexin-43+Caveolin-3 [Con43+Cav3] and Connexin-43+Troponin T [Con43+TnT]), of endothelial origin (EVs exposing VE-Cadherin [VE-Cad]) and EVs exposing inflammatory markers (myeloperoxidase [MPO] or pentraxin3 [PTX3]). Results: Median concentrations of EVs exposing Con43+TnT and Con43+Cav3 were approximately five to six times higher in coronary sinus compared to radial artery indicative of cardiac release. Patients with HFrEF had high transcoronary gradients of both Con43+TnT and Con43+Cav3 EVs, whereas HFpEF had elevated gradients of Con43+Cav3 EVs but lower gradients of Con43+TnT. Coronary sinus concentrations of both Con43+TnT and Con43+Cav3 correlated significantly with echocardiographic and laboratory measures of HF. MPO-EV concentrations were around two times higher in the right atrium compared to the coronary sinus, and slightly higher in HFpEF than in HFrEF. EV concentrations of endothelial origin (VE-Cad) were similar in all three patient groups. Conclusion: Con43+TnT and Con43+Cav3 EVs are released over the heart indicating cardiomyocyte origin. In HFrEF the EV release profile is indicative of myocardial injury and myocardial stress with elevated transcoronary gradients of both Con43+TnT and Con43+Cav3 EVs, whereas in HFpEF the profile indicates myocardial stress with less myocardial injury.